KAJIAN ETNOLINGUISTIK PADA ISTILAH PERTANIAN NANAS DI KABUPATEN KUBU RAYA - Sutriyadi Sutriyadi (Universitas Islam Zainul Hasan Genggong, 2026)
Abstract: This study examines the ethnolinguistic lexicon of pineapple farming terms in Sungai Malaya, Kubu Raya Regency, focusing on the form, meaning, and categories of words used by local farmers. The research method used is descriptive qualitative with field observation techniques and in-depth interviews with pineapple farmers in the area. The results of the study indicate that the lexicon used is divided into three main categories, namely nouns, verbs, and adjectives, with the dominance of nouns in terms of tools and land parts, and verbs in the cultivation process. In terms of meaning, the lexicon is divided into five classifications, namely the pineapple planting process, planting period, tools, pineapple fruit conditions, and land parts. This study reveals the richness of local culture and traditional knowledge recorded in the Kubu Raya Malay lexicon, and shows that pineapple farming terms reflect the physical and social environment of the local farming community. These findings are expected to be used as documentation and revitalization materials for regional languages, as well as contribute to the development of ethnolinguistic theory in Indonesia.